2023
DOI: 10.1002/uog.27458
|View full text |Cite
|
Sign up to set email alerts
|

Prediction using serum glycosylated fibronectin of imminent pre‐eclampsia in women with new‐onset hypertension

N. Sokratous,
M. Bednorz,
A. Wright
et al.

Abstract: ObjectiveTo compare the predictive performance for delivery with pre‐eclampsia (PE) within 2 weeks after assessment in women with new‐onset hypertension at 24–41 weeks' gestation between serum glycosylated fibronectin (GlyFn) concentration, serum placental growth factor (PlGF) concentration and soluble fms‐like tyrosine kinase‐1 (sFlt‐1) to PlGF concentration ratio.MethodsThis was a prospective observational study of 409 women with a singleton pregnancy presenting at 24–41 weeks' gestation with new‐onset hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In a previous study of women presenting with new‐onset hypertension at 24–41 weeks' gestation, we found that the predictive performance for delivery with PE within 2 weeks of presentation by GlyFn was similar to that of PlGF and the sFlt‐1/PlGF ratio, with a detection rate of about 60% at a screen‐positive rate of 46% and a false‐positive rate of 42% 17 . Although the screen‐positive and false‐positive rates in the women with new‐onset hypertension were much higher than those reported herein in women with chronic hypertension, the predictive performance in the two patient groups is similar, because, as shown in the ROC curves in Figure 2, the detection rate of superimposed PE by GlyFn in women with chronic hypertension is about 75%, at a false‐positive rate of 42%.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…In a previous study of women presenting with new‐onset hypertension at 24–41 weeks' gestation, we found that the predictive performance for delivery with PE within 2 weeks of presentation by GlyFn was similar to that of PlGF and the sFlt‐1/PlGF ratio, with a detection rate of about 60% at a screen‐positive rate of 46% and a false‐positive rate of 42% 17 . Although the screen‐positive and false‐positive rates in the women with new‐onset hypertension were much higher than those reported herein in women with chronic hypertension, the predictive performance in the two patient groups is similar, because, as shown in the ROC curves in Figure 2, the detection rate of superimposed PE by GlyFn in women with chronic hypertension is about 75%, at a false‐positive rate of 42%.…”
Section: Discussionmentioning
confidence: 59%
“…First, we examined the distribution of GlyFn concentration, PlGF concentration and sFlt-1/PlGF concentration ratio in the group of women who developed superimposed PE and those that did not. Second, we defined screen-positive groups using the recommended cut-off of 85 for the sFlt-1/PlGF ratio 24 and, to allow for comparison, cut-offs of 75 pg/mL for PlGF and 510 μg/mL for GlyFn were used, as described previously 17 . We found great disparity between the three tests in screen-positive rates so, to allow for a fair comparison between the tests, we found the cut-off for each test corresponding to a screen-positive rate of approximately 10%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies in women with chronic hypertension and in those presenting to specialist clinics with GH, we reported that the predictive performance for development of PE within the subsequent 2 weeks of serum GlyFn concentration was similar to that of PlGF concentration and sFlt‐1/PlGF concentration ratio 26,27 . However, the performance of all three tests was poor and their use is unlikely to improve the management of such women.…”
Section: Discussionmentioning
confidence: 82%